Condições atmosféricas conducentes à ocorrência de tempestades convectivas severas na América do Sul - Foss, Marilei (2011)
An investigation of the atmospheric environments prone to severe convective weather is conducted for the subtropics of South America, east of the Andes Mountain Range. Upper air soundings valid at 00Z and 12Z for six sounding sites in subtropical South America (namely, Porto Alegre/BRA, Florianópolis/BRA, Curitiba/BRA, Foz do Iguaçu/BRA, Resistência/ARG e Buenos Aires/ARG) are employed to generate a short 12-yr climatology (from January 1998 to December 2009) of some of the main necessary ingredients for severe thunderstorm development: moisture availability, conditional instability, and vertical wind shear (VWS). The goal of the climatology is to document the typical magnitudes and seasonal variability of those ingredients with the aid of convective parameters. Threshold magnitudes for such parameters were objectively determined (via quantile analysis) and tested as cut-off criteria utilized to discriminate the severe weather environments. To that end, classic North-American threshold values extracted from the literature were also tested and the results compared vis-à-vis the South-American counterparts. Distinct combinations of such thresholds were employed to select atmospheric profiles theoretically conducive to severe thunderstorms and tornadoes. Atmospheric profiles obtained from the NCEP-NCAR Reanalysis data valid at 18Z were also used. The time and space distribution of the selected severe weather profiles were examined, emphasizing the seasonal variation and geographic distribution. From these sampled profiles, composite analysis were built for and Principal Component Analysis were applied to relevant meteorological variables at distinct vertical levels in order to search for the associated synoptic-scale patterns. The climatology succesfully reproduced the expected seasonal behavior of parameters that are indicative of conditional instability and VWS. Compared to the North-American climatology, the magnitudes found for the 700-500hPa lapse rates, 0-6km bulk shear and height of the LCL were lower in South America. The seasonal variability and space distribution of the severe weather profiles suggest that there exists an equatorward [poleward] displacement of the severe weather activity as winter [summer] approaches. The synoptic pattterns associated with the severe weather environments is different from those traditionally recognized for North America, particularly at the surface.